Critical Thinking Behavior of Early Childhood in Project Based Learning: A Literature Review - Khairiyah, Umi; Hapidin, Hapidin; Wulan, Sri (Proceedings of International Conference on Science, Education, and Technology, 2025)
Critical thinking is one of the essential skills that children must possess to face the challenges of the 21st century. However, the 2018 Programme for International Student Assessment (PISA) result indicate that Indonesian children’s critical thinking skills remain low and rank below those of many other countries. One of the efforts that can be undertaken to improve this skill is the implementation of project-based learning. This literature review aims to examine and analyze the findings from recent empirical studies in the form of articles, journals and research documents regarding the impact and effectiveness of project-based learning in improving enhancing critical thinking skills among early childhood learners. The method used is qualitative descriptive, employing the Miles and Huberman model of data reduction, data presentation, and drawing conclusions. The articles reviewed are derived from various primary sources, including national journals published within the last five years and international journals published within the last eight years. All literature was carefully selected from various accredited, high-quality and reputable scientific databases. The review findings reveal that project-based learning is superior to conventional and other instructional models, as evidenced by improvements in children’s thinking patterns, creativity, conceptual and principled understanding, problem-solving, decision-making, and independence – all of which are integral components of critical thinking skills.